Exclusively cephalic venous access for cardiac resynchronisation: A prospective multi‐centre evaluation. Issue 12 (17th September 2020) - Harding, Idris; Mannakkar, Nilanka; Gonna, Hanney; Domenichini, Giulia; Leung, Lisa WM; Zuberi, Zia; Bajpai, Abhay; Lalor, Joseph; Cox, Andrew T.; Li, Anthony; Sohal, Manav; Chen, Zhong; et al.
Abstract: Background: Small series has shown that cardiac resynchronisation therapy (CRT) can be achieved in a majority of patients using exclusively cephalic venous access. We sought to determine whether this method is suitable for widespread use. Methods: A group of 19 operators including 11 trainees in three pacing centres attempted to use cephalic access alone for all CRT device implants over a period of 8 years. The access route for each lead, the procedure outcome, duration, and complications were collected prospectively. Data were also collected for 105 consecutive CRT device implants performed by experienced operators not using the exclusively cephalic method. Results: A new implantation of a CRT device using exclusively cephalic venous access was attempted in 1091 patients (73.6% male, aged 73 ± 12 years). Implantation was achieved using cephalic venous access alone in 801 cases (73.4%) and using a combination of cephalic and other access in a further 180 (16.5%). Cephalic access was used for 2468 of 3132 leads implanted (78.8%). Compared to a non‐cephalic reference group, complications occurred less frequently (69/1091 vs 12/105; P  = .0468), and there were no pneumothoraces with cephalic implants. Procedure and fluoroscopy duration were shorter (procedure duration 118 ± 45 vs 144 ± 39 minutes, P  < .0001; fluoroscopy duration 15.7 ± 12.9 vs 22.8 ± 12.2 minutes, P  < .0001). Conclusions: CRT devices can be implanted using cephalic access alone in a substantial majority of cases. This approach is safe and efficient.